Behavior of Conical Porous Hybrid Journal Bearing with Pseudoplastic Lubricant. Issue 3 (4th May 2021) - Sharma, Satish C.; Singh, Anil
Abstract: In recent years, porous bearings have been increasingly used in various industrial applications because they are less noisy, have good precision, and are relatively maintenance free. In this article, the numerical analysis of a conical porous hybrid journal bearing system (CPHJBS) has been carried out. The interactive effects of permeability parameter, semi cone angle, and pseudoplastic (shear thinning) lubricant behavior on the performance of CPHJBS have been theoretically investigated. The governing Reynolds equation for a non-Newtonian lubricant in the bearing clearance space of CPHJBS is solved using a finite element model. Findings of this study indicate that the CPHJBS operating with a pseudoplastic lubricant offers a higher value of stability threshold speed margin ( ω ¯ t h ) for the lower value of semi cone angle ( γ = 10 0 ) and lower value of permeability parameter ( Ψ = 0.005 ) .